An assessment on the auction market in Selangor - Zainudin, Farah Eleena; Mohamed Osman, Mariana; Muhamad Yusop, Siti Wahidah; Ibrahim, Mansor (e-International Publishing House, Limited, 2019)
The first auction legislation in Malaysia was enacted in the states of Penang and Malacca in 1906. The real estate market including auction market is considered an effective method in selling real estate properties (Chyi, 2015). Auction is one method in selling property in a quick way but this method is consider as force sales as most properties sold due to owner unable to pay the monthly mortgage to the bank. There are advantages of buying property in auction market where the buyer can get the property cheaper than market value and the property usually has a matured environment. The downside of purchasing an auction property is that the buyer is not allowed to view or inspect the inside of the property and sometimes the property is not vacant by the owner. The buyer need to conduct their own research first if they have the intention to buy auctioned property. Based on literatures, there are various considerations for buying auction properties such as the type of properties, the location, value, existing conditions, the existing facilities and infrastructure and many more. This aim of the study is to assess the issues and problems faced by buyers in housing auction market in Selangor. The objectives were to identify the preferred location among the respondents in selection their bidding units. It was found that among respondents, the most preferred location of auction properties was in Gombak. In term of issues and problem in buying auction properties, respondents claimed the issues are the long period of time in getting loan approved and released payment , the title and ownership issues, the units are still occupied by owner, the conditions of units and the overall cost that need to be prepare by buyers. It is hoped that this paper would guide decision maker and government in planning of the overall housing market in Malaysia as properties being auctioned is getting higher over time.